New potentially active pyrazinamide derivatives synthesized under microwave conditions - Jandourek, Ondrej; Dolezal, Martin; Kunes, Jiri; Kubicek, Vladimir; Paterova, Pavla; Pesko, Matus; Buchta, Vladimir; Kralova, Katarina; Zitko, Jan (Molecules (Basel, Switzerland), 2014)
A series of 18 N-alkyl substituted 3-aminopyrazine-2-carboxamides was prepared in this work according to previously experimentally set and proven conditions using microwave assisted synthesis methodology. This approach for the aminodehalogenation reaction was chosen due to higher yields and shorter reaction times compared to organic reactions with conventional heating. Antimycobacterial, antibacterial, antifungal and photosynthetic electron transport (PET) inhibiting in vitro activities of these compounds were investigated. Experiments for the determination of lipophilicity were also performed. Only a small number of substances with alicyclic side chain showed activity against fungi which was the same or higher than standards and the biological efficacy of the compounds increased with rising lipophilicity. Nine pyrazinamide derivatives also inhibited PET in spinach chloroplasts and the IC50 values of these compounds varied in the range from 14.3 to 1590.0 μmol/L. The inhibitory activity was connected not only with the lipophilicity, but also with the presence of secondary amine fragment bounded to the pyrazine ring. Structure-activity relationships are discussed as well.
Keywords: Photosynthesis; Microbial Sensitivity Tests; Inhibitory Concentration 50; Pyrazinamide; chloroplasty; Spinacia oleracea; antituberkulotika; Structure-Activity Relationship; vztahy mezi strukturou a aktivitou; antifungální látky; Hydrophobic and Hydrophilic Interactions; Microwaves; mikrobiální testy citlivosti; inhibiční koncentrace 50; pyrazinamid; Antitubercular Agents; Antifungal Agents; Mycobacterium tuberculosis; mikrovlny; herbicidy; transport elektronů; Chloroplasts; Candida albicans; Herbicides; fotosyntéza; Electron Transport; Staphylococcus epidermidis; hydrofobní a hydrofilní interakce